Effective control of particle size, surface plasmon resonance and stoichiometry of Cu@CuxO nanoparticles synthesized by laser ablation of Cu in distilled water. (December 2018) - Baruah, Prahlad K.; Sharma, Ashwini K.; Khare, Alika
Highlights: Synthesis of Cu@Cux O NPs by Pulsed laser ablation in liquid. Control on size and SPR of NPs by laser ablation duration and laser energy. Control on stoichiometry of the synthesized NPs. Structural elucidation of NP via SAED and Raman spectroscopy. Abstract: Pulsed laser ablation of copper in distilled water is used to synthesize copper nanoparticles as a function of duration of laser ablation and incident laser energy. Increase in the ablation time from 15 to 60 min at fixed incident laser energy of 30 mJ resulted in blue shift of the surface plasmon resonance peak from 641 to 626 nm along with a broadening of the plasmon bandwidth from 127 to 165 nm, respectively. The increase in incident laser energy from 30 to 70 mJ at fixed duration of 60 min ablation induced a similar blue shift in the plasmon peak from 626 to 617 nm and a corresponding increase in the bandwidth from 165 to 209 nm, respectively. These observations are due to reduction in the size of the nanoparticles as also confirmed by the transmission electron microscopic images. Nearly uniform particle size distribution is observed for an ablation time of 60 min. An increase in laser energy from 30 to 70 mJ keeping the ablation time fixed for 60 min resulted in decrease in the average size of the nanoparticles from 20 to 7 nm, respectively. The structural studies via selected area electron diffraction and Raman analysis revealed that the extent of oxidation taking place in the synthesized nanoparticles of Cu@Cux O also varies with the laser ablation duration and incident laser energy. For the samples prepared with 30 mJ of incident laser energy and laser ablation duration upto 30 min, Cu2 O phase of the nanoparticles is dominant whereas for an increased duration of 60 min at the same laser energy, there is an appearance of CuO phase. The increase in laser energy upto 70 mJ for 60 min of ablation duration resulted in CuO as the dominating phase. It has been established that by merely varying the laser ablation duration and the incident energy, particle size, plasmonic response and structural properties of the synthesized nanoparticles can be effectively tuned.